2019
DOI: 10.3389/fonc.2019.01398
|View full text |Cite
|
Sign up to set email alerts
|

Erastin Reverses ABCB1-Mediated Docetaxel Resistance in Ovarian Cancer

Abstract: Overexpression of drug efflux transport ABCB1 is correlated with multidrug resistance (MDR) among cancer cells. Upregulation of ABCB1 accounts for the recurrence of resistance to docetaxel therapy in ovarian cancer with poor survival. Erastin is a novel and specific small molecule that targets SLC7A11 to induce ferroptosis. In the present research, we explored the synergistic effect of erastin and docetaxel in ovarian cancer. We confirmed that the co-delivery of erastin with docetaxel significantly decreased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 40 publications
4
70
2
Order By: Relevance
“…Sorafenib is a multikinase inhibitor approved for the treatment of advanced cancer (e.g., hepatocellular carcinoma) [ 166 ], and it can be used as an agonist of ferroptosis for its inhibitory effect on system xc- [ 167 ]. More importantly, erastin, a more potent inhibitor of system xc-, has been shown to improve the anticancer activity of traditional chemotherapy drugs (e.g., docetaxel, cisplatin, and temozolomide) in several cancer cells [ 168 170 ]. Besides its promising role for cancer therapy, ferroptosis is also implicated in multiple forms of tissue damage, including ischemia/reperfusion injury [ 171 ], traumatic injury [ 172 ], and neurodegeneration [ 173 , 174 ].…”
Section: Regulation Of Iron Metabolism For Antitumor Immunitymentioning
confidence: 99%
“…Sorafenib is a multikinase inhibitor approved for the treatment of advanced cancer (e.g., hepatocellular carcinoma) [ 166 ], and it can be used as an agonist of ferroptosis for its inhibitory effect on system xc- [ 167 ]. More importantly, erastin, a more potent inhibitor of system xc-, has been shown to improve the anticancer activity of traditional chemotherapy drugs (e.g., docetaxel, cisplatin, and temozolomide) in several cancer cells [ 168 170 ]. Besides its promising role for cancer therapy, ferroptosis is also implicated in multiple forms of tissue damage, including ischemia/reperfusion injury [ 171 ], traumatic injury [ 172 ], and neurodegeneration [ 173 , 174 ].…”
Section: Regulation Of Iron Metabolism For Antitumor Immunitymentioning
confidence: 99%
“…Similarly, overexpression of ABCB1 (P-glycoprotein/MDR1) in ovarian cancers usually leads to chemo-resistance via intracellular drug export (104,105). Erastin can conspicuously reverse the ABCB1-mediated DTXL resistance by limiting the drug efflux activity of ABCB1 (80).…”
Section: Ferroptosis: a Sword To Reverse The Acquired Drug Resistancementioning
confidence: 99%
“…A recent study showed that Erastin can reverse the resistance of ovarian cancer cells to docetaxel by inhibiting the pump activity of ABCB1. The combined use of Erastin and docetaxel provides a new option for the treatment of ovarian cancer resistance (Zhou et al, 2019).…”
Section: Ovarian Carcinomamentioning
confidence: 99%